Application-oriented resource matching model based on trust for internet-based virtual computing environment - Chun-ge ZHU; Xin-ran LIU; Yi-xian YANG; Hong ZHANG (Tongxin xuebao)
In order to solve the problem of reasonable resource s ing in the virtual computing environment (iVCE),a resource matching model,based on trust “resource sliding window” model,was proposed.Firstly,the resources were classified in advance by their static properties.Then the resource nodes were evaluated by a trust model based on the time window and Bayesian algorithm,and the evaluated results as well as the resource load were fused to determine the levels of the dynamic real-time performance.Finally,the scheduling resources were allocated according to the comprehensive assessment of the static and dynamic properties of the resource nodes.The proposed model provides a basis of scheduling strategy for different resources with different tasks and attributes,thus achieving the goal of “proper resources’ serving proper tasks”.Simulation results show that,compared the previous scheduling algorithm,the proposed model has better performance in the success rate of task execution and the rate of resource utilization.